FORMULATION OF PEPPERMINT ESSENTIAL OIL AROMATHERAPY PREPARATIONS: A PRELIMINARY STUDY ON THE ORGANOLEPTIC - Amestiasih, Tia; Rizqi, Januar; Pramono, Cahyo; Widayati, Ririn Wahyu; Lintang, Dhea Cahya (Media Informasi, 2025)
Background: Peppermint oil has a distinctive refreshing aroma as well as analgesic, antispasmodic, and calming effects, making it suitable for use in aromatherapy. This study aims to develop formulations and evaluate the organoleptic properties of peppermint essential oil-based aromatherapy preparations, which are known to have therapeutic benefits in reducing stress, increasing alertness, and providing a relaxing effect. Method: The research method used a laboratory experimental approach with two formulations of different concentrations of peppermint essential oil, menthol, and olive oil. Organoleptic tests involved visual observation of shape, color, aroma, and sensation on the skin, along with pH measurements and preference tests on 40 respondents. Results: The results showed differences in organoleptic properties between the two formulations. The first formula was brown in color with a strong aroma, while the second formula was yellowish brown with a more fragrant and softer aroma, which was preferred by respondents. Both formulations gave a warm sensation on the skin, while pH measurements showed a range between 5 and 6, which is safe for the skin as per the pH standard of topical products (4.5-6.5). In the favorability test, the second formulation received higher preference from respondents, especially in terms of aroma and feel on the skin. Conclusion: this peppermint oil based aromatherapy formulation showed positive results in organoleptic aspects and pH safety, so it has the potential as a natural aromatherapy product that can be well received by consumers. This research opens up opportunities for further development regarding the stability and therapeutic potential of essential oil combinations in aromatherapy.